2020
DOI: 10.29333/ejmste/7860
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cluster Changes in Students’ Knowledge Structures Throughout General Chemistry

Abstract: Chemistry is traditionally perceived as difficult to comprehend. Its mastery requires that a variety of concepts be linked to form an organized knowledge system. The connections need to be made not only between the concepts associated with the macroscopic level of the chemistry triplet but also between the submicroscopic and symbolic levels. Many factors influence a learner's success in bridging concepts between these levels. In this study, the aim was to identify and examine the changes in general chemistry s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 44 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…Moreover, observing the overall patterns of how each gender organizes each representational level of chemistry reveals similarities in the organization of their knowledge structures. These findings indicate that extended chemistry triplet could be added as a layer to bring depth to the analysis of chemistry concept maps (Gulacar et al, 2020).…”
Section: Exploring Differences Between Male and Female Students' Concept Mapsmentioning
confidence: 87%
See 4 more Smart Citations
“…Moreover, observing the overall patterns of how each gender organizes each representational level of chemistry reveals similarities in the organization of their knowledge structures. These findings indicate that extended chemistry triplet could be added as a layer to bring depth to the analysis of chemistry concept maps (Gulacar et al, 2020).…”
Section: Exploring Differences Between Male and Female Students' Concept Mapsmentioning
confidence: 87%
“…The seventeen terms used in this study were classified using Becker's classification (2015) of each level based on inductive analysis, as well as the same classification schema determined by a group of chemistry professors and graduate and undergraduate students (Gulacar et al, 2019). Through this process, it has been found that chemistry terms can be classified with more than one representational level of chemistry (Gulacar et al, 2019(Gulacar et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations